A taxonomic revision of genus Labrundinia Fittkau, 1962 (Diptera: Chironomidae: Tanypodinae) - Da Silva, Fabio Laurindo; Fonseca-Gessner, Alaide Aparecida; Ekrem, Torbjørn (Zootaxa, 2014)
The species of the genus Labrundinia (Diptera: Chironomidae: Tanypodinae: Pentaneurini) are revised, described and figured. Keys to known adult males, pupae and larvae are provided. Fourteen previously known species are redescribed, and 25 species from Neotropical region are diagnosed and described as new to science. These species treated are L. amandae sp. n., L. amazonica sp. n., L. becki Beck et Beck, L. carolae sp. n., L. costaricae sp. n., L. fera Roback, L. fiorelinii sp. n., L. ﬁttkaui sp. n., L. fosteri Roback, L. hirsuta Roback, L. gregi sp. n., L. jasoni sp. n., L. johannseni Beck et Beck, L. kogilamae sp. n., L. longipalpis Goetghebuer, L. mayaca sp. n., L. meta Roback, L. multidentata sp. n., L. nathani sp. n., L. neopilosella Beck et Beck, L. nicaraguensis sp. n., L. opela Roback, L. panamensis sp. n., L. parabecki Roback, L. paraﬁttkaui sp. n., L. parareniformis sp. n., L. paravirescens sp. n., L. paulae sp. n., L. pilosella Loew, L. reniformis sp. n., L. robacki sp. n., L. semicurvata sp. n., L. setosa sp. n., L. separata Edwards, L. sofiae sp. n., L. tenata Roback, L. trilucida sp. n., L. unicolor sp. n., L. virescens Beck et Beck. A diagnosis of the genus is presented and morphological differences to closely related genera are discussed.